The Influence of Nursing Work Environment on Patient Safety. (August 2020) - Mihdawi, Maha; Al-Amer, Rasmieh; Darwish, Rima; Randall, Sue; Afaneh, Tareq
Background : Patient safety has been a concern over the past two decades. The value of nurses and their work environment in relation to patient safety has been acknowledged by studies and international organizations. This study aimed to examine the relationship between patient safety practices and the nursing work environment. Methods : In total, 570 registered nurses were invited from the inpatient units in public and private hospitals. Perceived patient safety was evaluated using the Overall Perceptions of Patient Safety subscale from the Hospital Survey of Patient Safety Culture (HSPSC). The nursing work environment was assessed using the Practice Environment Scale of the Nursing Work Index (PES-NWI). Findings : Of the 350 of 570 (64.6%) nurses surveyed, 35.2% (125) reported positive levels of perceived patient safety. Staffing and resource adequacy, professional communication style, and nurses' participation in hospital quality improvement activities were associated with higher levels of perceived patient safety. Conclusion/Application to Practice : This study provided empirical results about perceived patient safety culture in relation to nursing work environment. It is paramount to focus on specific dimensions of the nursing work environment, such as staffing and resource adequacy, nurses' participation and advancement, and communication style to improve the quality of care provided to patients. Hospitals are considered one of the most hazardous places compared with industries. Policy makers would help reduce injuries, save resources, and build a culture of safety when taking into consideration the importance of the nursing work environment in relation to patient safety.